Management of Education Implementation in Surakarta Inclusive Primary School - Nugraha, Andre Eksaputra; Minsih, M; Wulandari, Murfiah Dewi; Rahmawati, Laili Etika (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study aims to examine the implementation of inclusive education at SD Negeri Bromantakan, Surakarta, by exploring its cultural, policy, and practical dimensions. It seeks to identify the progress and challenges in promoting inclusivity for students with special needs. Methodology: A qualitative approach was employed, using interviews, observations, and document reviews to collect in-depth data. The Index for Inclusion was used as an evaluative framework to analyze school policies, cultural attitudes, and inclusive practices. Participants included teachers, school principals, and parents. Results: The findings reveal that the school has taken significant steps toward inclusivity, such as increasing learning time for students with special needs and encouraging parental involvement. However, major barriers persist, including discriminatory attitudes, weak inter-stakeholder collaboration, a shortage of Special Education Teachers (GPK), and limited teacher training. Although the school has implemented group seating arrangements and student-centered strategies under the Merdeka Curriculum, these efforts require further development. Applications/Originality/Value: This study underscores the need for enhanced teacher capacity building, deeper parental engagement, and policy refinement to support inclusive education. The research contributes valuable insights into the current state of inclusive practices in Indonesian primary schools and offers strategic recommendations for improvement.